2015
DOI: 10.2109/jcersj2.123.485
|View full text |Cite
|
Sign up to set email alerts
|

A bioactive glass nanocomposite scaffold toughed by multi-wall carbon nanotubes for tissue engineering

Abstract: Bioactive glasses have wide application prospects in bone replacement and regeneration owing to the unique osteoconductivity and osteostimulativity. However, the high brittleness and poor compressive strength limit their applications in load-bearing positions. In this study, multi-wall carbon nanotubes (CNTs) were used to toughen bioactive glass (1393 glass), and their nanocomposite scaffolds were fabricated by selective laser sintering. The effect of CNTs amount (15 wt.%) on mechanical properties of the scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Ball milling is a high-energy technique in which collisions between small rigid spheres generate extreme pressures capable of dispersing CNT within matrix materials. In one instance, ball milling was used in conjunction with ultrasonication to toughen a bioactive glass nanocomposite scaffold with CNT ( Liu et al, 2015 ). An ultrasonicated CNT-ethanol solution was mixed with bioactive glass nanoparticles, and the wet mixture was subject to a high energy ball milling machine.…”
Section: Fabrication Of Cnt-based Scaffoldsmentioning
confidence: 99%
“…Ball milling is a high-energy technique in which collisions between small rigid spheres generate extreme pressures capable of dispersing CNT within matrix materials. In one instance, ball milling was used in conjunction with ultrasonication to toughen a bioactive glass nanocomposite scaffold with CNT ( Liu et al, 2015 ). An ultrasonicated CNT-ethanol solution was mixed with bioactive glass nanoparticles, and the wet mixture was subject to a high energy ball milling machine.…”
Section: Fabrication Of Cnt-based Scaffoldsmentioning
confidence: 99%
“…Results showed that both CNTs-HA and graphene-HA materials supported cell growth and differentiation. Liu et al [191] used CNTs as reinforcement fillers to enhance the mechanical properties of bioglass scaffolds including compressive strength (maximum value of 37.32 MPa for samples containing 3 wt% of CNTs) and fracture toughness (maximum value of 1.58 MPa m 1/2 for samples containing 3wt% of CNTs). Scaffolds were produced using a powderbed fusion additive manufacturing system.…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
“…However, when the amount of nanomaterial was greater than an optimum level of loading (different in each case), the effect was reduced. Liu et al [ 277 ] reported that 3 wt.% MWCNTs presented the most pronounced effect in terms of mechanical properties for BG-based scaffolds. In the case of Di, following the study by Shuai et al [ 278 ], this level of loading was reduced to 2 wt.% MWCNTs.…”
Section: 3d Printed Scaffolds With Carbon-based Nanomaterialsmentioning
confidence: 99%